"A brave new (digital) world"? Effects of in-house social media on HRM - Stefan Hauptmann; Thomas Steger (Zeitschrift für Personalforschung (ZfP), 2013)
Social media offer many opportunities for organizations but present, at the same time, many challenges, too. Particular attention must be paid to the new patterns of behavior emerging in organizations. We argue that these patterns derive both from the technical characteristics of the virtual environment and also from specific social structural conditions currently emerging. By referring to two case studies, we want to highlight and discuss the implications of these current developments and their opportunities, threats and consequences for Human Resource Management. Our analysis will be supported by theories and research on the reproduction of rules and norms, on the one hand, and on social structural studies about digital natives and Generation Y, on the other. In order to sharpen our argument and to highlight the challenges of social media for human resource management, we propose the concept and notion of a 'parallel world.' – – Die Nutzung von Social Media bietet viele Möglichkeiten für Organisationen, aber auch zahlreiche Herausforderungen. Vor allem die Emergenz neuer Verhaltensmuster seitens der Organisationsmitglieder gilt es zu berücksichtigen. Diese, so unsere Argumentation, lassen sich sowohl aus den technischen Besonderheiten virtueller Umgebungen als auch aus besonderen, gegenwärtig emergierenden sozialstrukturellen Konstellationen herleiten. Dies hat auch Konsequenzen für das Personalmanagement, was in dem vorliegenden Beitrag anhand zweier Fallstudien exemplifiziert und diskutiert werden soll. Argumentativ gestützt wird die Analyse von Theorien und Studien zur Reproduktion von Regeln und Normen einerseits, und sozialstrukturellen Studien zu Digital Natives bzw. zur Generation Y andererseits. Zur scharfen Konturierung gegenüber der Offline-Welt mit Blick auf das Personalmanagement schlagen wir vor, Social Media mit Attributen einer 'Parallelwelt' zu versehen.
Keywords: D01; D04; D02; M14; M15; O15; 650; social media; computer-mediated communication; digital natives; group-coherence; organizational structures; rule-following; Intranet; Web 2.0-Technologien; Verhalten in Organisationen; Personalmanagement; Deutschland